2009
DOI: 10.1104/pp.109.150250
|View full text |Cite
|
Sign up to set email alerts
|

Thylakoid Protein Phosphorylation in Higher Plant Chloroplasts Optimizes Electron Transfer under Fluctuating Light    

Abstract: Several proteins of photosystem II (PSII) and its light-harvesting antenna (LHCII) are reversibly phosphorylated according to light quantity and quality. Nevertheless, the interdependence of protein phosphorylation, nonphotochemical quenching, and efficiency of electron transfer in the thylakoid membrane has remained elusive. These questions were addressed by investigating in parallel the wild type and the stn7, stn8, and stn7 stn8 kinase mutants of Arabidopsis (Arabidopsis thaliana), using the stn7 npq4, npq4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
232
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 240 publications
(253 citation statements)
references
References 45 publications
20
232
0
1
Order By: Relevance
“…Using normal white light, however, the excitation balance between PSII and PSI provided by steady-state LHCII phosphorylation is essential only for plants grown under light intensity fluctuations [41]. Furthermore, we have observed that the excitation balance provided by steady-state LHCII phosphorylation under fluctuating light is a key factor in maintaining the activity of PSI, but not PSII [42].…”
Section: The Facts and Enigmas In Photoprotectionmentioning
confidence: 69%
See 3 more Smart Citations
“…Using normal white light, however, the excitation balance between PSII and PSI provided by steady-state LHCII phosphorylation is essential only for plants grown under light intensity fluctuations [41]. Furthermore, we have observed that the excitation balance provided by steady-state LHCII phosphorylation under fluctuating light is a key factor in maintaining the activity of PSI, but not PSII [42].…”
Section: The Facts and Enigmas In Photoprotectionmentioning
confidence: 69%
“…The traditional use of different qualities of low intensity light to study state transitions contradict the natural redox regulation of the thylakoid protein kinases and phosphatases in plant chloroplasts, leading to a full dephosphorylation (state I) or a full phosphorylation (state II) of both the PSII and LHCII phosphoproteins. LHCII phosphorylation and dephosphorylation by different intensities of white light, however, does not lead to such state transitions, apparently owing to opposite behaviours of the PSII core and LHCII protein phosphorylation under these light conditions [41,79]. We have provided evidence that LHCII phosphorylation establishes a common antenna bed for both PSII and PSI in the so-called thylakoid megacomplexes [80], which ensure proper distribution of excitation energy to PSII and PSI.…”
Section: Interplay Between Npq Photosynthetic Control and Lhcii Phosmentioning
confidence: 86%
See 2 more Smart Citations
“…48,54 Furthermore, when pgr5 mutants were grown under naturally fluctuating light in the field, they showed higher mortality rates as compared to WT (Fig. 1), whereas no difference between pgr5 and WT was observed when seedlings were grown under constant light.…”
Section: Photosynthesis Control Is Essential For Plant Viabilitymentioning
confidence: 99%